Pressmud-enriched phosphatic fertilisers: A sustainable approach to improving sugarcane yield and soil quality - Porkodi, G; Babu, M; Anand, G; Sugumaran, M P; Ramamoorthy, P; Basker, M; Abirami, R; Madhana, K P (Plant Science Today, 2026)
Sugarcane is a nutrient-exhaustive crop that demands efficient phosphorus (P) management, yet conventional mineral fertilisers often suffer from low use efficiency due to soil fixation. Phosphatic fertilisers, produced by fortifying sugar industry byproducts such as pressmud with mineral phosphates and inoculating them with phosphate-solubilising bacteria (PSB), offer a sustainable alternative that can improve P availability, crop productivity and economic returns. A field study was conducted on sugarcane variety CoC 13339 under tropical conditions to evaluate the efficiency of different enriched P formulations in comparison with conventional sources. The main objectives of this study were to evaluate the effect of sources and rates of phosphorus on available P content in soil, compare the efficiency of pressmud along with different sources of phosphatic fertilisers and evaluate the effects of enriched phosphatic fertilisers and their levels on growth and yield of sugarcane. Growth attributes, sugarcane yield, juice quality, nutrient uptake and soil nutrient status were monitored across crop growth stages. The results demonstrated that integrated organic mineral fertilisers enriched with pressmud and supported by PSB consistently enhanced Olsen-P levels, improved yield components and increased cane productivity. These findings highlight the potential of recycling agro-industrial residues into enriched fertilisers for sustainable nutrient management and yield enhancement in sugarcane. Future studies should focus on long-term field validation across ratoon cycles, nutrient dynamics in diverse soil types and integration with climate-smart management practices to support large-scale adoption.